My Baby: Optimalisasi Pemantauan Pertumbuhan Balita dan Edukasi Gizi Berbasis Aplikasi Digital - Miftahul Jannah; Putri Rahayu Ratri; Dessya Putri Ayu; Ria Chandra Kartika; Surya Dewi Puspita; Yohan Yuanta; Muhammad Adi Saputro (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Growth monitoring of under-five children is an important effort for early detection of growth disorders. However, growth monitoring activities at Community Health Center (CHC) still face several challenges, including manual data recording, limited interpretation of measurement results, and suboptimal nutrition education media for parents. The utilization of digital technology through mobile health applications is an alternative approach to improve the effectiveness of child growth monitoring. This study aimed to develop and evaluate the feasibility of the My Baby application as a digital media for growth monitoring and nutrition education among under-five children. This study employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted in Sucopangepok Village, Jelbuk District, Jember Regency, from May to December 2025. The application trial involved 14 respondents consisting of 1 village midwife and 13 CHC cadres. Data were collected using a feasibility evaluation questionnaire and analyzed descriptively. The results showed that the My Baby application was successfully developed with features including child identity recording, anthropometric measurement recording in both offline and online modes, nutritional status interpretation, growth charts, nutrition education materials, two user dashboards (mother and cadre dashboards) and export data into Microsoft Excel. The feasibility evaluation showed that the application achieved a score of 90.3%, categorized as highly feasible. The application was considered easy to use, informative, and beneficial in supporting child growth monitoring and CHC recording activities. The My Baby application has the potential to serve as a digital supporting medium for primary healthcare services in early detection of growth disorders.